MENGEMBANGKAN KEMAMPUAN MENGENAL HURUF ABJAD MELALUI PEMBELAJARAN MENGGUNAKAN MEDIA BULBINCA PADA ANAK-ANAK KELOMPOK A TK DARUT TAQWA KOTA KEDIRI - Novita Happy Nur Laili; Khan, Rosa Imani; Hanggara Budi Utomo; Lestariningrum (QURROTI, 2024)
This research was motivated by the lack of development of the ability to recognize alphabet letters in group A children at Darut Taqwa Kindergarten, Kediri City, which was caused by a lack of tools or media for learning to recognize alphabet letters that were able to attract children's attention. The problem to be solved in this research is "Can learning using Bulbinca Media develop the ability to recognize letters of the alphabet in group A children of Darut Taqwa Kindergarten, Kediri City, academic year 2023/2024?" The subjects in this study were 17 children, consisting of 9 boys and 8 girls. This research uses Kemmis & Taggard's Classroom Action Research (PTK) design. The characteristic of this classroom action research is that it is carried out in cycles. Each cycle consists of planning, implementing actions, observing and reflecting. Data collection instruments in this research used teaching modules, children's performance assessment sheets and learning activity observation sheets. Based on the results of this research, it can be concluded that learning using Bulbinca Media has been proven to be able to develop the ability to recognize letters of the alphabet in group A children of Darut Taqwa Kindergarten, Kediri City for the 2023/2024 school year. This is evidenced by the increase in the percentage of learning completeness from pre-action to cycle II, namely pre-action by 35%, cycle I by 59% and cycle II by 76%. Because the success/completion of classical learning in learning the ability to recognize alphabet letters using Bulbinca Media Cycle II has exceeded 75%, there is no need for the research to continue to Cycle III.